The Revelation and Delegation Principles in Common Agency Games - David Martimort; Lars Stole (Center for Economic Studies and ifo Institute (CESifo), 2001)
In the context of common agency adverse-selection games weillustrate that the revelation principle cannot be applied to studyequilibria of the multi-principal games. We then demonstrate thatan extension of the taxation principle - what we term the delegation principle - can be used to characterize the set of allcommon agency equilibria.
Keywords: 330; revelation principle; delegation principle; taxationprinciple; common agency; adverse selection.